2001
DOI: 10.2105/ajph.91.6.947
|View full text |Cite
|
Sign up to set email alerts
|

Papanicolaou test screening and prevalence of genital human papillomavirus among women who have sex with women

Abstract: A B S T R A C TObjectives. The purpose of this study was to examine frequency of and attitudes toward Papanicolaou (Pap) test screening in women who have sex with women (WSW) and to determine prevalence of genital human papillomavirus (HPV).Methods. Women were eligible if they reported having engaged in sex with another woman in the preceding year. Medical and sexual histories were obtained. Cervical specimens for Pap tests and cervical and vaginal specimens for HPV DNA testing were collected.Results. HPV DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(49 citation statements)
references
References 29 publications
4
43
0
1
Order By: Relevance
“…26 Further, it is possible that the factors potentially driving cervical cancer screening disparities between WSW and non-WSW, including heterosexism in the healthcare system 15,16,19,50 and misperceptions among women and healthcare providers that WSW are not at risk of HPV or cervical cancer, 1517,19,51 also underlie the lower odds of HPV vaccine initiation between girls and women with only female past-year sexual partners and those with only male past-year sexual partners. Moreover, other studies have shown that healthcare providers’ and parents’ endorsement of the HPV vaccine, which may vary based on girls’ and young women's sexual orientation, 26 was positively associated with HPV vaccine initiation among young U.S. women.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…26 Further, it is possible that the factors potentially driving cervical cancer screening disparities between WSW and non-WSW, including heterosexism in the healthcare system 15,16,19,50 and misperceptions among women and healthcare providers that WSW are not at risk of HPV or cervical cancer, 1517,19,51 also underlie the lower odds of HPV vaccine initiation between girls and women with only female past-year sexual partners and those with only male past-year sexual partners. Moreover, other studies have shown that healthcare providers’ and parents’ endorsement of the HPV vaccine, which may vary based on girls’ and young women's sexual orientation, 26 was positively associated with HPV vaccine initiation among young U.S. women.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the meantime, healthcare facilities, schools, and public health departments and organizations can implement programs that promote knowledge of HPV and cervical cancer risk from male and female sexual partners throughout the life course among young women, caregivers, and healthcare providers 1517,19,51 and facilitate access to opt-out HPV vaccination services among adolescent and young adult women with only female and no sexual partners.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other research has also shown WSW, particularly those who report never having had a sexual experience with a man, are less likely to receive a pap smear compared to heterosexually identified women (Marrazzo & Gorgos, 2012). Repeatedly, WSW cite the reason for not receiving a pap smear as not having had sex with men ( Bailey, Kavanagh, Owen, McLean, & Skinner, 2000; Kerker, Mostashari, & Thorpe, 2006; Marrazzo et al, 1998; Marrazzo, Koutsky, Kiviat, Kuypers, & Stine, 2001), and many have had this confirmed as unnecessary by their physicians (Marrazzo, 2004; Waterman & Voss, 2015). Marrazzo and Gorgas, among others, have called for research on patterns of seeking preventive sexual health care among WSW (Marrazzo & Gorgos, 2012).…”
Section: Introductionmentioning
confidence: 99%